Estrategia para el fortalecimiento de las políticas de gestión estratégica del talento humano en el marco de implementación del modelo integrado de planeación y gestión en la Gobernación de Boyacá - Fuquen Fonseca, Diego Fernando; Medina Chisaba, Víctor Javier (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: The objective of this work is to formulate strategies to strengthen the strategic management policy of human talent in the implementation of the integrated planning and management model in the Government of Boyacá. Said work was approached by means of a methodological strategy with a mixed approach whose method is descriptive and cross sectional. The study population for this research work are public officials of all organizational levels of the Government of Boyacá, who will be subjected to a non-probabilistic sampling by quotas. As main results, it was sought to review the state of the art of the last ten years about the trends of thThe objective of this work is to formulate strategies to strengthen the strategic management policy of human talent in the implementation of the integrated planning and management model in the Government of Boyacá. Said work was approached by means of a methodological strategy with a mixed approach whose method is descriptive and cross sectional. The study population for this research work are public officials of all organizational levels of the Government of Boyacá, who will be subjected to a non-probabilistic sampling by quotas. As main results, it was sought to review the state of the art of the last ten years about the trends of the strategic management of human talent in public institutions. Subsequently, a diagnosis was made of the dimension of human talent in each of the organizational levels of the entity, taking into account the four main ones. Then, the contributions and experiences of senior managers during the implementation process were identified. of the GETH policy. Finally, some strategies are proposed aimed at the continuous improvement of the GETH policy implementation processes for the year 2022.e strategic management of human talent in public institutions. Subsequently, a diagnosis was made of the dimension of human talent in each of the organizational levels of the entity, taking into account the four main ones. Then, the contributions and experiences of senior managers during the implementation process were identified. of the GETH policy. Finally, some strategies are proposed aimed at the continuous improvement of the GETH policy implementation processes for the year 2022.